1995
DOI: 10.1177/0887302x9501300302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Field-Wear Abrasion on Barrier Properties of Nonwoven Fabrics

Abstract: One of a series of papers from the S-208 Regional Research Committee. Abstract Eight nonwoven fabrics were made into experimental protective pants and worn into two types of low crop fields. Barrier properties (water penetration resistance, oil repellency, and air permeability) were measured for control fabrics and fabrics taken from pants worn in the field Results indicate that while loss of breaking strenth due to abrasion was minimal, effects of field wear on barrier properties were significant. Water penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Furthermore, abrasion of wet and dry specimens did not have notable effect on the liquid barrier properties. However, previous research indicated lower abrasion resistance [43] and more liquid penetration [44] for wet specimens in comparison with dry specimens. This inconsistency was attributed to the difference in the method and level of applied abrasion and types of fabrics.…”
Section: Wear and Abrasionmentioning
confidence: 90%
“…Furthermore, abrasion of wet and dry specimens did not have notable effect on the liquid barrier properties. However, previous research indicated lower abrasion resistance [43] and more liquid penetration [44] for wet specimens in comparison with dry specimens. This inconsistency was attributed to the difference in the method and level of applied abrasion and types of fabrics.…”
Section: Wear and Abrasionmentioning
confidence: 90%
“…Occupational workers are normally involved in physical activities, and consequently the fabric may become abraded (Rezazadeh & Torvi, 2011). Therefore, some researches have been conducted to examine the property degradation of thermal protective clothing by using the garments that have been subjected to simulated frictional abrasion, which resulted from wearers’ activities like crawling and hose handling (Cloud & Lowe, 1995; Wang et al, 2021). Chen and Cloud (2000) studied the effects of abrasion treatments on liquid barrier properties of chemical protective clothing.…”
mentioning
confidence: 99%